2016
DOI: 10.1039/c5cs00516g
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Lewis acids: emerging reactivity and applications in catalysis

Abstract: Part of the renaissance in main group chemistry has been a result of the focus on reactivity. This has led to the development of applications in stoichiometric reactivity and catalysis. In this tutorial review, we focus attention on the role of phosphorus-based Lewis acids in such advances. While early literature recognizes the role of P(iii) and P(v) electrophiles in coordination chemistry, it has generally been more recent studies that have focused on applications of this Lewis acidity. Applications of these… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
174
0
6

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 277 publications
(181 citation statements)
references
References 49 publications
1
174
0
6
Order By: Relevance
“…Recent efforts have shown that electrophilic phosphorus( v ) compounds 13 can be used as Lewis acid catalysts for organic reactions 1418 as well as in FLPs for hydrogenations 19 and CO 2 capture reactions. 20 Inspired by these advances and using fluoride anion affinity data as a guide, 21,22 several groups have paid a renewed attention to the properties of antimony( v ) compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts have shown that electrophilic phosphorus( v ) compounds 13 can be used as Lewis acid catalysts for organic reactions 1418 as well as in FLPs for hydrogenations 19 and CO 2 capture reactions. 20 Inspired by these advances and using fluoride anion affinity data as a guide, 21,22 several groups have paid a renewed attention to the properties of antimony( v ) compounds.…”
Section: Introductionmentioning
confidence: 99%
“…21 In addition, we find 2 is polymorphic and compare the structures of 2α, initially reported by Kisenyi et al,22 with the new polymorph 2 in relation to 1 and other dithia-chloroarsoles. Treatment of 2 with the Lewis acids MCl3 (M = Al, Ga) affords the iso-morphous pair of dithia-arsolidinium cations [3] MCl4] (3a M = Al, 3b M = Ga) in which the cations are located on a crystallographic mirror plane. Addition of 2 to LiN SiMe3)2 in a 3 : 1 ratio leads to formation of the paddlewheel complex 4 (Scheme 1) which exhibits supramolecular aggregation through close S⋯S contacts.…”
mentioning
confidence: 99%
“…In earlier work by Müller and coworkers, they obtained the analogous species with the bulkier mTer iPr ligand by the reaction of the NHC-stabilized hydridosilylene with elemental sulfur [62]. BmTer iPr features the same 1 JSiH coupling constant (209 Hz), which is smaller compared to the one of silathioformamide (255 Hz) reported by Driess and coworkers. [50].…”
Section: Reaction Of Silyliumylidene a With H2smentioning
confidence: 96%
“…Low-valent main group chemistry is a rapidly developing field and the wealth of new structural motifs, which have been isolated in the past two decades, have increasingly gained interest in using these species for the activation of small molecules and, potentially, for catalysis (for representative reviews see [1][2][3][4][5][6][7]). Key to these developments have been the usage of suitable synthetic methodologies in combination with thermodynamic and kinetic stabilization by appropriately chosen ligands.…”
Section: Introductionmentioning
confidence: 99%